The Translation of Directive Acts by Fansub in The Boss Baby 1 Movie - Ma'ruf, Muhammad Hafizd; Ardi, Havid (English Language and Literature, 2024)
This study aims to identify the type of directive act and technique of translating directive act of the movie entitled The Boss Baby 1 Movie. The design of this study is descriptive qualitative method. The data of this study is the utterance of directive act of The Boss Baby 1 movie translated from English to Indonesia. The data was analyzed by applying the theory of Searle and vandervekens to classifying the types of directive act and use the theory Molina and Albir to classifyng the translation technique used by translator in translating directive act. The results of this study found that there are 6 types of directive acts found from 199 data. Command was the most dominant type of directive  act found which is 112 data (56.28%). Followed by question (15.08%), instruction (10.05%), requestive (7.04%), and suggest (6.03%), meanwhile the types of directive act that are slightly found is invitation (5.53%). Meanwhile, there are 5 types of directive act translation techniques found from 216 data. The most dominant translation technique found was established equivalence in 191 data (88.43%). While the least frequent types of translation techniques are compensation, modulation techniques with 2 data (0.93%).